Determinants of participation in colorectal cancer screening among community-dwelling Chinese older people: Testing a comprehensive model using a descriptive correlational study. - Leung, Doris Y.P.; Wong, Eliza M.L.; Chan, Carmen W.H. (European Journal of Oncology Nursing, 2016)
Purpose The prevalence of colorectal cancer (CRC) among older people is high. Screening for CRC presents a cost-effective secondary prevention and control strategy which results in a significant reduction in mortality. This study aims to describe the prevalence of CRC screening and examine its risk factors among Chinese community-dwelling older people guided by a comprehensive model combining Health Belief Model and Extended Parallel Processing Model. Methods A descriptive correlational study was conducted. A convenience sample of 240 community-dwelling adults aged ≥60 was recruited in May–July in 2012 in Hong Kong. Participants were asked to complete a questionnaire which collected information on demographic variables, CRC-related psychosocial variables and whether they had a CRC screening in the past 10 years. Results Among the participants, 25.4% reported having a CRC screening test. Results of logistic regression analyses indicated that participants with a higher level in cue to action, and lower perceived knowledge barriers and severity-fear were significantly associated with participation in CRC screening. But there were no significant associations between fatalism and cancer fear with screening. Conclusions The prevalence of CRC screening was low in Hong Kong Chinese community-dwelling elders. A number of modifiable factors associated with CRC screening were identified which provides specific targets for interventions. This study also adds to the knowledge regarding the associations between fatalism and fear with CRC screening behaviors among Chinese older people.